2001
DOI: 10.2202/1949-6605.1137
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Social Commitments of College Students

Abstract: ❖ Developmental orientations as measured by the Dakota Inventory of Student Orientations (DISO) are strong predictors of the social attitudes and commitments that college students make. The aim of this study was to investigate the nature of social beliefs and commitments during the college years in relation to developmental orientations as measured by DISO (Lavelle & Rickord, 1999). Results supported CreativeReflective scale scores as predictive of commitment to the more humanitarian issues such as race and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…There are several models of college student development. One widely recognized and utilized model in the student services field is the Dakota Model (Lavelle & O'Ryan, 2001). The Dakota Model of College Student Development was developed based on factor analysis of 738 students' responses to various items such as career beliefs and social beliefs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several models of college student development. One widely recognized and utilized model in the student services field is the Dakota Model (Lavelle & O'Ryan, 2001). The Dakota Model of College Student Development was developed based on factor analysis of 738 students' responses to various items such as career beliefs and social beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years the focus has been on creating small group environments that promote opportunities for personal growth and development in both academic and social spheres. In a study of 102 freshmen at a large Midwestern university Lavelle and O'Ryan (2001) found that smaller groups promote intimacy and more complete development of the students. These small groups created a family type of environment that also encouraged students' involvement and increased their ability to adjust to college in the social realm.…”
Section: Discussionmentioning
confidence: 99%